Pendidikan Berbasis Motivasi - Nurliana Nurliana; Miftah Ulya (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2019)
The education traditional focuses on the imposition method namely teaching by pouring out things that are considered important by the teacher for students. This method does not consider learning given according to ability. Since discoveries about human personality and behavior, the development of the education sector has begun to change. Human behavior is driven by certain motives, the act of learning is successful if it is based on motivation. To move actions requires motivation. With motivation, someone has passion, desire, planning, targets that will be realized, motivation as a drive-in human. The millennial era, with all facilities including educational innovations using various media and forms of a strategy used, but the educational process has not been realized according to educational goals. Due to a lack of motivation possessed by students. As a result, it is less keratin, less innovative, not solutive. This is the phenomenon of education today. So that research on motivation-based education needs to be done, is an offer of discussion that is urgent for the world of education today. The motivating learning motivation includes: First, the teacher as an Inspirator can inspire students. Second, Giving clear objectives, through the material presented. Third, the teacher must be able to guide and provide solutions to each obstacle.